A NEW ANALYTICAL TOOLS FOR SAFE MOTHERHOOD PROGRAMS AND HEALTHY - Benavides, Bruno (2015)
Maternal mortality is a major public health problem in Peru and other developing countries. This problem does not only mean the deaths of hundreds of thousands of women each year, but that has as one of its effects the mortality rate among children of these women and expresses the deep inequalities between countries and within them, between regions, social classes and géneros1. There is growing consensus on the basic strategies to successfully address this situation. However, it is crucial to identify the unique characteristics of maternal mortality in each country and, within them, in each region. From a program management perspective, the relationship between supply and demand for services is a key to understanding the patterns of maternal mortality and conclude prioritization decisions and planning element.